Awareness of physical changes occurring in adolescent period: an interventional study among girls 13-17 years of age in rural field practice area Government Medical College, Amritsar - Jyoti, Kamal; Mahajan, Sanjeev; Singh, Dhalwinder; Gupta, Arti (International Journal Of Community Medicine And Public Health, 2025)
Background: Adolescence is a crucial period of life having stress and storms. It is the important period of development that follows the onset of puberty during which a young person develops from a child into an adult. During this transitional stage that extends from 10-19 years, there occurs physical and psychological development that follows the period of puberty leading to adulthood. This study aimed to assess the awareness of physical changes among adolescent girls to assess the awareness of physical changes among adolescent girls. Methods: This interventional study was carried out in the rural area of Amritsar, two government senior secondary schools were selected by simple random technique. In these schools adolescent girls of the age group 13 to 17 years were included and out of school adolescent girls of the same age group who were residents of these two villages were also included in the study. The study was carried out in three phase pre intervention, intervention and post intervention phase. Results: Before intervention 45.21% of the respondents did not know and after intervention 68.26% came to know that 10-19 is the age group under adolescence periods. Before intervention respondents 32.17% had no knowledge and after intervention 53.34% had good knowledge. Conclusions: Information education and communication sessions significantly increases the knowledge of adolescent girls about physical changes occurring in this period.